2010
DOI: 10.1007/s11095-010-0255-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Gene Silencing in Transgenic EGFP Mice Using Aerosolised Chitosan/siRNA Nanoparticles

Abstract: This work provides a technology platform for effective pulmonary delivery and gene silencing of RNAi therapeutics with potential use in preclinical studies of respiratory disease treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 32 publications
(39 reference statements)
1
55
0
1
Order By: Relevance
“…Moreover, promising results were obtained upon inhalation of free siRNA in human clinical trials for the treatment of patients infected with respiratory syncytial virus [36]. However, recent publications have clearly demonstrated the benefit of nanocarriers for siRNA inhalation therapy [9,32,37]. This was confirmed by our work, as the aspiration of free siRNA in the bronchoalveolar lumen of BALB/c mice resulted in negligible siRNA internalization by rAM and hence also failed to elicit a gene silencing effect.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, promising results were obtained upon inhalation of free siRNA in human clinical trials for the treatment of patients infected with respiratory syncytial virus [36]. However, recent publications have clearly demonstrated the benefit of nanocarriers for siRNA inhalation therapy [9,32,37]. This was confirmed by our work, as the aspiration of free siRNA in the bronchoalveolar lumen of BALB/c mice resulted in negligible siRNA internalization by rAM and hence also failed to elicit a gene silencing effect.…”
Section: Discussionsupporting
confidence: 74%
“…As seen in Figure 2, nanoparticles containing EGFP-specific siRNA, were able to remarkably decrease the fluorescence ratio compared to the mismatch formulation, naked siRNA and the non-treated group. There was no significant difference in the fluorescence ratio between naked siRNA and nanoparticle/siRNA mismatch treated mice [94]. Interestingly, the same siRNA delivery system was proposed as an easy-to-use freeze-dried formulation for potential biomedical applications and longer shelf-life therapeutics.…”
Section: Effect Of Phmentioning
confidence: 98%
“…Results showed that 43 and 37% knockdown in EGFPexpressing bronchiole epithelial cells compared to untreated mice and EGFP-mismatch control, respectively [65]. Following that, local lung delivery using a non-invasive intratracheal insertion of a nebulizing catheter, was implemented into mice (chitosan Mw = 170 kDa, DD = 84%) [94]. The evaluation of aerosol lung deposition and gene silencing in H1299 cells (N/P = 57) revealed that aerosolization altered neither particle size nor silencing efficiency of the tested formulation at 50 nM of siRNA, which further showed minimal effect on cell viability compared to the TransIT-TKO  siRNA Interestingly, the same transfection behavior was observed in vivo, using transgenic green mice, with increased particle distribution in bronchial and alveolar regions and at much lower siRNA amounts (EGFP silencing = 68% compared to mismatch group) compared with intranasal administration (N/P = 23).…”
Section: Effect Of Phmentioning
confidence: 99%
“…Similarly, glycol chitosan-polyethylenimine nanoparticles had been shown to inhibit expression of RFP in RFP/B16F10-bearing mice thus showing higher tumor-targeting ability [112]. Nielsen et al have recently shown that aerosolized chitosan/siRNA nanoparticles could be used for gene silencing in transgenic EGFP mouse lungs [113]. Thus, based on the literature it is evident that chitosan and its derivatives have enhanced properties in terms of DNA interaction, condensation, and intracellular gene delivery.…”
Section: Sirna Delivery By Chitosan Derivativesmentioning
confidence: 99%